PEMBUATAN SISTEM VAKUM OTOMATIS GAS H2S BERBAHAN TiO2-Ni/Al2O3 TERKONEKSI ARDUINO UNO PADA LABORATORIUM KIMIA - Jacson Victor Morin; Darma Santi (Jurnal Natural, 2021)
Research has been carried out on the H2S gas sensor made of TiO2-Ni/Al2O3 which is connected to an automatic vacuum. The results showed that the optimum conditions for the variation of Ni doping metal levels were 20 mg / gram TiO2. The semiconductor material synthesis method used the sol gel method with TTiP precursor which was made at pH 7. Coating of the sol gel solution on the Al2O3 substrate used a dip coater with a decrease speed of 1 cm / minute and was carried out 7 times of immersion. The characterization of synthetic results used UVVis, XRD, FTIR and SEM-EDX. The band gap value resulting from Ni doping is 2.75 eV from 3.2 eV, XRD identification shows that TiO2 is anataseic and detected at 2θ. FTIR data also supports XRD results with detection of TiO2, Ni-O, NiTiO3, Ti-O-Ni, and Ti-O-Ti groups. TiO2-Ni / Al2O3 sensor test results are very sensitive and selective to H2S gas. Arduino Uno sensor and microcontroller connectivity can change the unit of resistance into a unit of ppm concentration and can drive the exhaust (vacuum) automatically in the laboratory room or chemical storage space when there is H2S.